A2.12 Phenotype Changes of Blood Eosinophils Reflect Activity and Severity in Systemic Sclerosis. (25th February 2013) - Wuttge, Dirk M; Andreasson, Annika; Tufvesson, Ellen; Scheja, Agneta; Hesselstrand, Roger; Truedsson, Lennart
Abstract : Background and Objectives: We investigated whether surface marker expression analysis of blood eosinophils may reflect disease activity in systemic sclerosis (SSc), since a role for eosinophils in the pathogenesis of SSc may be suggested from the observation of increased counts in bronchoalveolar lavage. Materials and Methods: By flow cytometer analysis, eosinophils in whole blood were identified in 32 consecutive untreated patients using surface marker CD16 and CD9. Surface expression of markers CD11b, CD44, CD48, CD54, CD81 and HLA-DR was measured. Data were related to clinical measurements of the disease activity. Results: An increased blood eosinophil population with low surface expression of CD9 was identified in patients with early SSc, i.e. a disease duration of <2 years, compared to patients with longer disease duration ( P = 0.003) and controls ( P = 0.029). CD81 expression was lower in SSc patients compared to healthy individuals ( P = 0.003). In patients with early SSc, CD81 levels correlated inversely to degree of skin involvement ( r = –0.67; P = 0.009). CD48 levels were increased in early SSc and were associated with an increased concentration of alveolar nitric oxide in these patients ( r = 0.84; P < 0.001). CD16 expression on blood eosinophils was also higher in patients with early disease and was associated with loss of nailfold capillaries ( r = –0.78; P < 0.001). Conclusions: Blood eosinophils in patients with SSc display a diverse phenotype depending on disease duration. In early disease, surface marker expression on eosinophils is associated with disease activity and severity.